PEMBERIAN HAK ATAS TANAH TERHADAP TANAH NEGARA PADA KANTOR PERTANAHAN KOTA SEMARANG - Dika Anggoro Putra, Hj. Endang Sri Santi, Triyono (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Land Rights for State land can be given to an individual or a legal entity according to the allocation and needs, which can include Property, Broking and Right to Use. Research Objectives know Granting Rights to Land on State land, the problems that often arise and how to overcome them. Methods normative juridical approach to the study area of Semarang Land Office. The research subjects are those involved in the provision of State Land Rights. Primary and secondary data obtained through literature study and field survey with data collection tool is the study of legislation and qualitative analysis of unknown processes Wawancara.Berdasarkan Granting Rights to Land on State land, in principle, is going according to the legislation in force. But in fact there are still problems that arise, namely the issuance of Decision Granting Rights to Land State still on time. To overcome given a very clear explanation to the applicant and the parties resolved to be guided by the principle objection Kontradiktur Dilimatie which deal in setting the boundaries of land, the people and the community aware of the importance of legal certainty.